Free radical scavenging capacity and cytotoxic and antiproliferative effects of Vaccinium meridionale Sw. agains colon cancer cell lines (2014)
ABSTRACT: Vaccinium meridionale Swartz, of the family Ericaceae, is commonly known as mortiño or agraz. The plant is considered a functional food, with a content of anthocyanins and antioxidants similar to or greater than that reported for other Vaccinium species. However, little is known about its nutraceutical and medicinal properties. Objectives: determine the antioxidant activity and cytotoxic and antiproliferative effect of mortiño fruit aqueous extract against colon adenocarcinoma cells (SW480) and their derived metastatic cells (SW620). Methods: total phenols and anthocyanins were determined by the Folin-Ciocalteu method. Caffeoyl derivatives were determined by HPLC-DAD. Antioxidant activity was analyzed as the ability to scavenge reactive oxygen species (ROS), reactive nitrogen species (RNI), peroxyl radicals and hydroxyl radicals. Cytotoxic and antiproliferative activities were studied by MTT and sulforhodamine B. Results: the following substances were found in 100 g of lyophilized extract: total phenols (2 546 mg GAE), anthocyanins (150.7 mg C3G), chlorogenic acid (126 mg), ferulic acid (108 mg) and coumaric acid (63 mg). Hydroxyl radical scavenging capacity was 36 147.5 μmol DMSO, whereas ROS and RNS scavenging capacity was 29 255.9 y 41 775.2 μmolTrolox, respectively. ORAC value was 41 775.2 μmolTrolox. A dose-dependent cytotoxic and antiproliferative effect was observed. IC50 value was 59.12 μg/ml for SW480 and 56.10 μg/mL for SW620. Conclusions: mortiño fruit aqueous extract exhibited antioxidant, cytotoxic and antiproliferative activities comparable to those of other berries of the genus Vaccinium, which could be partly explained by the presence of a high content of anthocyanins and phenolic acids.